2013
DOI: 10.2147/dddt.s44496
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected effects of peripherally administered kynurenic acid on cortical spreading depression and related blood–brain barrier permeability

Abstract: Cortical spreading depression (CSD) involves a slowly-propagating depolarization wave in the cortex, which can appear in numerous pathophysiological conditions, such as migraine with aura, stroke, and traumatic brain injury. Neurons and glial cells are also depolarized transiently during the phenomena. CSD is followed by a massive increase in glutamate release and by changes in the brain microcirculation. The aim of this study was to investigate the effects of two N-methyl-D-aspartate receptor antagonists, end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In addition to PIP, BBB paracellular permeability has been observed to increase during familial hemiplegic migraine and in animal models of migraine ( Gursoy-Ozdemir et al, 2004 ; Dreier et al, 2005 ; Olah et al, 2013 ). In a model of cortical spreading depression (CSD), Evans blue and plasma protein extravasation was associated with an increase in MMP-9 expression and activity and a decrease in ZO-1 expression in brain microvessels ( Gursoy-Ozdemir et al, 2004 ).…”
Section: Tight Junction Alterations In Neurological Disordersmentioning
confidence: 99%
“…In addition to PIP, BBB paracellular permeability has been observed to increase during familial hemiplegic migraine and in animal models of migraine ( Gursoy-Ozdemir et al, 2004 ; Dreier et al, 2005 ; Olah et al, 2013 ). In a model of cortical spreading depression (CSD), Evans blue and plasma protein extravasation was associated with an increase in MMP-9 expression and activity and a decrease in ZO-1 expression in brain microvessels ( Gursoy-Ozdemir et al, 2004 ).…”
Section: Tight Junction Alterations In Neurological Disordersmentioning
confidence: 99%
“…Quite apart from the neuroimmunological activity of quinolinic acid, it can increase the permeability of the bloodbrain barrier (149)(150)(151)(152), an effect intriguingly opposed by kynurenic acid (153). Not only would this allow inflammatory mediators easier access to the CNS cells but it would also facilitate passage of leukocytes directly into the brain parenchyma.…”
Section: Alzheimer's Disease and Multiple Sclerosismentioning
confidence: 99%
“…Therefore, the neuroprotective property of KYNA could be due to its antagonistic activity toward the NMDA receptor [15], and/or anti-inflammatory and antioxidant effects [39,40]. Previous studies have shown that KYNA crosses the blood brain barrier poorly [29,30]. It was therefore reasonable to assume similar poor crossing through the blood retinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the KYNA is neuroprotective in the retina, we first investigated whether it is permeable to the blood retinal barrier, although KYNA has been reported to be poorly permeable to the blood brain barrier [29,30]. We injected KYNA intravenously into WT mice and measured its levels in the serum and retina after 2 h. We found a significant increase in KYNA levels both in serum and retinas of KYNA injected mice compared to sodium phosphate buffer-injected control mice (Supplementary Figure S1).…”
Section: Administration Of Kyna Inhibited I/r Injury-mediated Rgc Losmentioning
confidence: 99%